Surveillance of carbapenem-resistant Klebsiella pneumoniae in Chinese hospitals - A five-year retrospective study - Xiaoyuan Qu; Haipeng Wang; Chaoran Chen; Zhimin Tao; Chang Yin; Aitian Yin; Chunyan Ma; Adi Idris (Journal of Infection in Developing Countries)
Introduction: Antibiotic consumption is associated with the development of antibiotic resistance. Our aim was to study the relationship between antibiotic consumption and carbapenem-resistant Klebsiella pneumoniae (CRKP) in three public general tertiary hospitals from 2011-2015 in the eastern, western and central regions of China.